PENGGUNAAN METODE PROJECTED UNIT CREDIT DAN ENTRY AGE NORMAL DALAM PEMBIAYAAN PENSIUN - Ayu Hapsari Budi Utami; Yuciana Wilandari; Triastuti Wuryandari (Jurnal Gaussian, 2012)
One effort to anticipate the risk of old age is to include every worker in a pension plan. From that pension plan, workers will get a pension benefit at retirement. Before reaching retirement age, there should be an actuarial cost, which includes the normal cost and actuarial liabilities. Both are calculated using actuarial cost methods. Actuarial cost methods are divided into two major categories, are Accrued Benefit Cost Method and Projected Benefit Cost Method. One example of the methods included in Accrued Benefit Cost Method is Projected Unit Credit Method, and one of the methods included in Projected Benefit Cost Method is Entry Age Normal Method. The data used in this thesis are secondary data from PT Taspen (Persero) KCU Semarang. The results of the calculation shows normal cost using Projected Unit Credit method continues to increase with increased salary. Whereas if using Entry Age Normal Method the same amount for each year on an employee. Besides, actuarial liability using Projected Unit Credit Method is smaller than using Entry Age Normal for each employee in each year.